DMA Application to Identify Students’ Decision-Making Ability Profiles - Murtafiah, Wasilatul; Lestari, Nurcholif Diah Sri; Lukitasari, Marheny (International Journal of Technology and Education Research, 2024)
This study aims to develop and validate a Decision Making Assesment (DMA) application to identify and enhance students' decision-making skills in mathematics learning, particularly among pre-service mathematics teachers at Universitas PGRI Madiun. The research employed a Research and Development (R&D) approach using the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation stages. The application was designed to assess higher-order thinking processes such as identifying problems, generating ideas, clarifying solutions, and evaluating their feasibility. During the development phase, the application underwent expert validation involving three experts in mathematics education, instructional media, and assessment. The average validation score was 3.57, indicating the application is valid. In the implementation phase, 94% of student respondents expressed positive perceptions, reflecting the application's high practicality. Effectiveness was confirmed by 92% of lecturers who reported that the application supported students’ decision-making development. These findings highlight the application's potential to foster active, reflective, and systematic reasoning processes through mobile learning. Furthermore, it aligns with 21st-century educational demands by integrating digital technology into authentic mathematics learning contexts. The study contributes to the innovation of digital-based assessment tools that support cognitive engagement and pedagogical relevance in higher education mathematics instruction.